CORDARONE AND VERAPAMIL EFFECTIVENESS IN PRE-HOSPITAL TREATMENT OF ATRIAL FIBRILLATION PAROXYSMS - V. G. Epifanov; V. T. Dolgikh; G. I. Zhuravlev; A. V. Shustov (Российский кардиологический журнал)
In 263 patients with atrial fibrillation lasting for 0,5–30 hours, pre-hospital antiarrythmic therapy (cordarone 5 mg/kg, verapamil 5–10 mg) was ineffective in the first hour. Sinus rhythm was restored in 8,8% and 11,5% of the patients receiving cordarone and verapamil, respectively. The majority of atrial fibrillation paroxysms were terminated in the first 24 hours (>90%). Cordarone and verapamil were equally effective in pre-hospital treatment of atrial fibrillation. Verapamil reduced ventricular rate more effectively.